Domestication and Improvement in the Model C4 Grass, Setaria - Hu, Hao; Mauro-Herrera, Margarita; Doust, Andrew N. (Frontiers in Plant Science, 2018)
Setaria viridis (green foxtail) and its domesticated relative Setaria italica (foxtail millet) are diploid C4 panicoid grasses that are being developed as model systems for studying grass genomics, genetics, development, and evolution. According to archaeological evidence, foxtail millet was domesticated from S. viridis approximately 9,000 to 6,000 YBP in China. Under long-term human selection, domesticated foxtail millet developed many traits adapted to human cultivation and agricultural production. In comparison with its wild ancestor, foxtail millet has less vegetative branching, reduced grain shattering, delayed flowering time and loss of photoperiod sensitivity. Foxtail millet is the only present-day crop in the genus Setaria, although archeological records suggest that other species have been domesticated and later abandoned in the last 10,000 years. We present an overview of domestication in foxtail millet, by reviewing recent studies on the genetic regulation of several domesticated traits in Setaria, and discuss how the Setaria system could be further developed to both understand its domestication history better and to provide more tools for future breeding efforts.